Animal rights. A challenge for Law, morality, and politics - Lalatta Costerbosa, Marina (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
Philosophical reflection on justice for animals finds expression in a multiplicity of theories. In this context are fundamental the theories focused on suffering and compassion (developed among others by Peter Singer and Carol Adams), Tom Regan’s theory of animal rights, Will Kymlicka’s political theory of animal rights. This paper identifies three open questions, transversal to the different positions that make up this rich and important debate. It deals with the notion of person, the theme of gratuitous moral evil, the presumed principle of reciprocity between rights and duties. The belief underlying the article is that an in-depth study of these theoretical issues could be fruitful in consolidating the idea that justice for animals is an unavoidable goal for every democracy.